STUDI ETNOBOTANI TUMBUHAN BERKHASIAT OBAT YANG DIMANFAATKAN MASYARAKAT SUKU MELAYU KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Ufara Qasrin; Agus Setiawan; Yulianty Yulianty; Afif Bintoro (Jurnal Belantara, 2020)
Medicinal plants have long been used by traditional communities, one of them is the Malay people in Lingga Regency, Riau Islands Province in healing various diseases. This study aims to determine the types of medicinal plants based on local knowledge of the indigenous Malay people. The population of this research is the native Malay people of Lingga Regency and the sampling is done using the snowball sampling method so that the selected respondents are following the required data. This type of research is descriptive research with qualitative and quantitative methods. The qualitative method was used to find out the use of medicinal plants used by the community by interview while the quantitative method was used to find out the percent of the use of medicinal plants by the Malays from the interviews. Based on the results of the study there were 102 types of medicinal plants in 53 families. The most commonly used plant parts are leaves (45.10%) by boiling and the least used are seeds and bark (1.96%). The most used habitats were herbs (27.45%) and trees (26.47%) and the least used were liana (8.82%) and terna (3.92%). Diseases that are usually treated by people with plants are diseases that are commonly suffered by ordinary people such as fever, diarrhea, coughing, toothaches, itching and mouth sores.